PERLINDUNGAN HUKUM BAGI PENANAMAN MODAL ASING (PMA) DI INDONESIA - Elman Simangunsong (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2019)
The existence of Foreign Investment in Indonesia is very important and strategic in supporting the implementation of national economic development and increasing economic growth in the community. Foreign investment is regulated in Law Number 25 of 2007. What is the legal protection for foreign investment in Indonesia, both for investment in the form of Limited Liability Company (PT) or investment. this shows that foreigners in Indonesia who carry out their capital investment activities are regulated by law and protected by the government under the law. The formulation of the problem is: How is the position of the establishment of foreign investment companies in Indonesia, What are the procedures for the implementation of foreign investment in Indonesia? What efforts have been made by the government if there is a violation of law in foreign investment in Indonesia? descriptive research. The data used are primary data and secondary data consisting of primary, secondary and tertiary legal materials. Data collection is done by interview and literature study. Data processing is done by examining data, analysis in this research is descriptive, which describes systematically conducting field research to obtain data. The results show that in every foreign company that wants to invest in Indonesia, it must take principle permission to the Investment Coordinating Board (BKPM). ) And the One Stop Integrated Investment and Services Office (PTSP). so that the company can be established in Indonesia and its establishment in accordance with the procedures of the law on foreign investment so that the foreign investment company is fully under the responsibility and supervision of the Republic of Indonesia. The government also gives relief to foreign investment in Indonesia in freeing the entry tax fees for goods or electronic equipment for foreign investment (PMA) in Indonesia in investing their capital.